1998
DOI: 10.1002/hep.510270606
|View full text |Cite
|
Sign up to set email alerts
|

Aly/Aly mice: A unique model of biliary disease

Abstract: An autosomal recessive murine mutation, coined ''aly/ aly'' or ''alymphoplasia,'' was recently reported. Homozygotes for aly are defective in both humoral and cellmediated immune function and have diffuse lymphoid cell infiltration of various tissues, particularly around the conduit ducts of the pancreas and salivary glands. In pilot studies in our laboratories, aly/aly mice were found to have peculiar biliary tract lesions, which were analyzed histologically and immunohistochemically in the present study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Histological examination revealed that virtually all organs were infiltrated with mononuclear cells. Consistent with results obtained from Nik aly/aly mice (33), these infiltrates contained CD3 + T-cells (Fig. 1F and G); importantly, however, the infiltrates also contained eosinophilic granulocytes, as confirmed by MBP staining, which were dominating in all organs investigated (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Histological examination revealed that virtually all organs were infiltrated with mononuclear cells. Consistent with results obtained from Nik aly/aly mice (33), these infiltrates contained CD3 + T-cells (Fig. 1F and G); importantly, however, the infiltrates also contained eosinophilic granulocytes, as confirmed by MBP staining, which were dominating in all organs investigated (Fig.…”
Section: Resultssupporting
confidence: 90%
“…We could not evaluate the liver for GVHD because aly/aly mice develop spontaneous hepatic inflammation that is difficult to distinguish from GVHD. 40 Taken together, these data show that GVHD can develop in the complete absence of LN and PP, as well as in recipients without LN, PP, and spleen. However, that GVHD is markedly reduced in aly/aly Spl Ϫ recipients relative to mice that have either LN, PP, or spleen indicates that these are important sites for donor T-cell priming that are redundant among themselves.…”
mentioning
confidence: 60%
“…24 Spontaneous multiorgan disease, including biliary and portal tract destruction, occur in MRL/lpr mice and aly/aly mice, 25,26 but it is unclear that inflammation in these mice is initiated by T-cell recognition of biliary antigens. Nonsuppurative inflammatory cholangitis and portal inflammation is seen in mdr2 knockout mice, apparently because the biliary tree is exposed to bile salts uncomplexed with phospholipid.…”
Section: Discussionmentioning
confidence: 99%